Newly Diagnosed Hepatic Encephalopathy Presenting as Non-convulsive Status Epilepticus: A Case Report and Literature Review - Marco Olivero; Delia Gagliardi; Delia Gagliardi; Gianluca Costamagna; Daniele Velardo; Francesca Magri; Fabio Triulzi; Giorgio Conte; Giacomo P. Comi; Giacomo P. Comi; Stefania Corti; Stefania Corti; et al. (Frontiers in Neurology, 2022)
BackgroundHepatic encephalopathy is characterized by psychiatric and neurological abnormalities, including epileptic seizure and non-convulsive and convulsive status epilepticus. Conventional brain magnetic resonance imaging is useful in supporting diagnosis since it can reveal specific radiological findings. In the literature, there is no description of hepatic encephalopathy onset as non-convulsive status epilepticus; we provide the first report.Case SummaryWe report a case of a 67-year-old woman, without history of cirrhosis, presenting altered mental state, normal brain computed tomography imaging, and electroencephalography suggestive of epileptic activity. We suspected non-convulsive status epilepticus, and we administered diazepam and levetiracetam with clinical improvement. Thus, we made a diagnosis of non-convulsive status epilepticus. A radiological study with brain magnetic resonance imaging showed bilateral hyperintensity on T1-weighted sequences of globus pallidus and hyperintensity of both corticospinal tracts on T2-weighted fluid-attenuated inversion recovery sequences. Blood tests revealed hyperammonemia, mild abnormality of liver function indices, and chronic Hepatitis B and D virus coinfection. Hepatic elastosonography suggested liver cirrhosis. The patient started antiviral therapy with entecavir and prevention of hepatic encephalopathy with rifaximin and lactulose; she was discharged with a normal mental state.ConclusionsHepatic encephalopathy can present as an initial manifestation with non-convulsive status epilepticus. Electroencephalography is useful for differentiating non-convulsive status epilepticus from an episode of hepatic encephalopathy, and neuroimaging aids the diagnostic process.